2013
DOI: 10.1007/978-3-642-30648-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field and Convection in the Cool Supergiant Betelgeuse

Abstract: We present the outcome of a highly-sensitive search for magnetic fields on the cool supergiant Betelgeuse. A time-series of six circularly-polarized spectra was obtained using the NARVAL spectropolarimeter at Télescope Bernard Lyot (Pic du Midi Observatory), between 2010 March and April. Zeeman signatures were repeatedly detected in cross-correlation profiles, corresponding to a longitudinal component of about 1 G. The time-series unveils a smooth increase of the longitudinal field from 0.5 to 1.5 G, correlate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…In a parallel study, Aurière et al (2010) detect a weak magnetic field, at the Gauss-level, at the surface of α Ori and this is so far the only RSG star for which a direct detection has been obtained. A follow-up study also A&A 603, A129 (2017) shows that this surface magnetic field appears to vary on a monthly time-scale (Bedecarrax et al 2013;Petit et al 2013) in agreement with the convective patterns time-scale (Freytag et al 2002;Montargès et al 2015).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…In a parallel study, Aurière et al (2010) detect a weak magnetic field, at the Gauss-level, at the surface of α Ori and this is so far the only RSG star for which a direct detection has been obtained. A follow-up study also A&A 603, A129 (2017) shows that this surface magnetic field appears to vary on a monthly time-scale (Bedecarrax et al 2013;Petit et al 2013) in agreement with the convective patterns time-scale (Freytag et al 2002;Montargès et al 2015).…”
Section: Introductionmentioning
confidence: 58%
“…For active stars, emission can be seen in the core of these lines. Petit et al (2013) report no emission in the core of these lines for α Ori and no significant indication of activity. In our own study, we also found no sign of activity in these lines for µ Cep.…”
Section: µ Cepmentioning
confidence: 84%
“…Two 0.22 nm-wide rectangular bandpasses V Hα and R Hα , centred on 655.885 and 656.730 nm respectively, were used for the continuum flux in the red and blue sides of the Hα line. The TBL CaIRT-index, following Petit et al (2013), was determined using using Eqn. 3 .…”
Section: Tbl Activity Indices For Hd 35296mentioning
confidence: 99%
“…While local dynamos are probably active in all stars with convective zones, their direct observational signatures may only be detectable in the most evolved objects (cool supergiants), for which the larger pressure scale height results in much larger convective cells (Schwarzschild 1975). This last type of magnetism is presumably responsible for the weak magnetic field detected at the surface of the slowly rotating supergiant Betelgeuse Petit et al 2013). A&A 556, A43 (2013) Observations are obviously essential for deciding between these different scenarios (that may act independently or together, depending on the object) or unveil other possible physical explanations for the manifestations of atmospheric activity recorded in cool, evolved stars.…”
Section: Introductionmentioning
confidence: 99%